2012
DOI: 10.1071/mf12119
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation in the structure of mangrove forests with respect to seawalls

Abstract: Artificial structures, such as seawalls, are increasingly disrupting the transition zones between terrestrial and marine systems. They can impede the transport of resources across habitat boundaries and impact adjacent sedimentary ecosystems by modifying hydrodynamics which, in turn, influence sedimentology and erosion. We assessed how structural elements of Avicennia marina mangrove forests along the Parramatta River estuary, Sydney, Australia, differ in the presence or absence of a seawall on the landward si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…(Currin et al 2008;Bilkovic and Mitchell 2013). Reductions in productivity in salt marsh (Freiss et al 2008) and mangrove (Heatherington and Bishop 2012) ecosystems were also associated with seawalls (Box 1b). However, Wong et al (2011) observed positive responses to armoring in low-energy habitats, reporting that the presence of both sills (Box 1a) and bulkheads (Box 1b) led to greater secondary production in salt marshes in North Carolina than in habitats without the added structure.…”
Section: E5: Productivitymentioning
confidence: 98%
“…(Currin et al 2008;Bilkovic and Mitchell 2013). Reductions in productivity in salt marsh (Freiss et al 2008) and mangrove (Heatherington and Bishop 2012) ecosystems were also associated with seawalls (Box 1b). However, Wong et al (2011) observed positive responses to armoring in low-energy habitats, reporting that the presence of both sills (Box 1a) and bulkheads (Box 1b) led to greater secondary production in salt marshes in North Carolina than in habitats without the added structure.…”
Section: E5: Productivitymentioning
confidence: 98%
“…In addition, seawalls destroy sea-to-land connectivity and impact mangrove forests by disrupting hydrodynamic patterns, organism movements, nutrient flows and modifying sediment balance [1,[43][44][45]. Mangrove forests constrained on their landward side by a seawall often contain less leaf litter and have fewer saplings than forests without seawalls [70]. Moreover, aquaculture (shrimp or fish farming) can reduce mangrove growth rates, increase mangrove mortality rates, and lead to ecological degradation through excess pond waste materials in sediments discharged from nearby aquaculture ponds [67,71].…”
Section: Root Cause Of Mangrove Degradation-seawall Constructionmentioning
confidence: 99%
“…For instance, despite the numerous ecosystem services they provide to urban communities (Benzeev et al 2017), mangrove forests are cleared in many coastal areas to make way for urban development (Harper et al 2007, Martinuzzi et al 2009, Lai et al 2015, Richards and Friess 2016. Where urban mangroves are left intact, they are vulnerable to deleterious effects from artificial structures constructed nearby; mangrove forests adjacent to seawalls tend to be narrower, with less leaf litter and fewer saplings than those without seawalls (Heatherington and Bishop 2012). Coral reefs and seagrass beds are also frequently built over (Chou 2006, Burt et al 2013, Yaakub et al 2014b).…”
Section: Loss Of Foundation Speciesmentioning
confidence: 99%